In-vitro antidiabetic activity of Malaxisrheedei SW (whole plant): An endangered medicinal orchid - RENJINI HARIDAS; SUMATHI P; SANGEETH THEKKAN (International Journal of Pharma and Bio Sciences, 2017)
To investigate the in vitro anti-diabetic potential of Malaxis rheedei SW whole plant methanol extract. This study evaluates the anti-diabetic potential of M. rheedei whole plant via in vitro inhibition of α-amylase and α-glucosidase using the methanol extract. The methanol extract of M. rheedei displayed the most effective inhibition of both α-amylase and α-glucosidase activities with half-maximal inhibitory concentration (IC50) of 407.56 µg/ml (α-amylase inhibitory activity) and 380.66 µg/ml (α- Glucosidase inhibitory activity).The observed inhibitions of α-amylase and α-glucosidase proved that the whole plant extract of M. rheedei have the potential to manage Diabetes mellitus but it is not a cure for Diabetes.